Transparent ceramic fiber and preparation method thereof
After mixing the ceramic powder with a ball mill such as photosensitive resin, roll grinding and extrusion photocuring treatment, long-distance transparent ceramic fibers are prepared, which solves the problems of surface roughness and poor optical performance in traditional processes, and achieves stable preparation of high-quality and long-distance fibers.
Patent Information
- Application Number
- CN202411893549.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
It is difficult to prepare long-distance transparent ceramic fibers in the prior art. Traditional processes have problems such as rough surfaces and poor optical performance, making it difficult to meet the research needs and industrial production needs of ceramic fibers.
After mixing ceramic powder, photosensitive resin, dispersant and initiator ball mill, homogenize roll milling through a 3D roller mill to form a ceramic slurry. Then, extrusion photocuring is performed in an extrusion molding machine to form a molded fiber wire material, and the transparent ceramic fiber is obtained by glue discharge and sintering.
The continuous extrusion preparation of high aspect ratio and low defective ceramic fibers is achieved. The fiber length is controllable, the surface is uniform, and the optical performance is excellent, which reduces the subsequent processing needs and has industrial prospects.
Smart Images

Figure CN119638381A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical material preparation, and in particular to a transparent ceramic fiber and a preparation method thereof. Background Art
[0002] As the heart of the laser, the gain medium determines the output power and light conversion efficiency. Fiber as a laser gain medium has the advantages of high stability, good beam quality, and high conversion efficiency, and can be widely used in medical, information communication, sensing and other fields. At present, the gain medium of fiber lasers is mostly quartz glass / single crystal. Quartz glass has good optical properties, low loss and high durability, which meets the requirements of many applications, but has low thermal conductivity. During the operation of the laser system, spontaneous emission (ASE) will occur, which will eventually lead to insufficient output power during long-term operation. The development and application of single crystal fiber are limited by high energy consumption, high cost, complex preparation, and especially the difficulty of high doping concentration. Therefore, it is necessary to study new fiber laser gain media.
[0003] Transparent ceramics have been proven to be an efficient and economical laser gain medium. The slope efficiency (η) of the 1at.% Nd:YAG ceramic sample reported in 2007 was as high as 65%, which was attributed to the fact that YAG ceramics have no segregation coefficient and can therefore be doped at a higher level than single crystals without doping losses. In addition, transparent ceramics have high fracture toughness and low preparation temperature (1750-1850°C), making them excellent candidates for gain media of fiber lasers.
[0004] However, there are few reports on transparent ceramic fibers. In 2011, Kim, Fair and others from the U.S. Air Force Laboratory successfully prepared ceramic fibers with a diameter of 30μm by using transparent ceramic materials, ushering in the era of transparent ceramic fibers. In 2017, they used SF57 glass cladding on the ceramic fiber and conducted laser experiments, achieving a maximum power of 0.7W at 2091nm, a slope efficiency of 7%, and a pumping threshold of less than 500mW. The laser output verified the feasibility of ceramic materials as a gain medium for fiber lasers. This experimental scheme is expected to enable fiber lasers to develop towards smaller size, lighter weight, higher working efficiency and higher reliability.
[0005] At present, the preparation method of ceramic fiber is mainly liquid molding, including several processes such as slip casting and 3D printing. In the two colloidal molding processes of slip casting and gel casting, due to the existence of surface tension of the slurry, it is difficult to inject the slurry into a small-aperture gypsum mold, and it may even form holes in the blank, and the surface is rough. The length of the prepared ceramic fiber depends on the design of the mold, and the preparation of long fibers is limited. The maximum molding length reported so far is 113mm; 3D printed ceramic fibers have high precision, but they are also limited by the model and are difficult to use in the preparation process of long fibers. The above molding methods are far from meeting the needs of ceramic fiber research and preparation and the needs of future industrial production. Therefore, in the preparation of large aspect ratio and long-distance ceramic fibers, it is an urgent problem to propose a reasonable preparation process and improve production efficiency. Summary of the invention
[0006] The technical problem to be solved by the present invention is how to prepare long-distance transparent ceramic fibers.
[0007] The present invention solves the above technical problems through the following technical means:
[0008] A method for preparing a transparent ceramic fiber comprises the following steps:
[0009] S1, ball-milling ceramic powder, photosensitive resin, dispersant and initiator to obtain a mixture; wherein the mass ratio of the ceramic powder, photosensitive resin, dispersant and initiator is 81-84:13-16.5:0.8-4.2:0.3-0.8;
[0010] S2, roller-milling the obtained mixture to obtain a ceramic slurry;
[0011] S3, extruding the obtained ceramic slurry in a preheated extrusion device, and passing through a light source for curing to obtain a formed fiber filament;
[0012] S4, debinding and sintering the obtained shaped fiber filaments to obtain the transparent ceramic fiber.
[0013] Preferably, in S1, the ceramic powder is a mixture of one or more of alumina powder, yttrium oxide powder and magnesium oxide powder.
[0014] Preferably, the ceramic powder is a mixture of yttrium oxide powder and aluminum oxide powder in a molar ratio of 3:5.
[0015] Preferably, in S1, the photosensitive resin is a mixture of one or more of hydroxyethyl acrylate HEA, 1,6-hexanediol diacrylate HDDA, and trimethylolpropane triacrylate TMPTA.
[0016] Preferably, in S1, the dispersant is one of CPD01 and CPD02 or a mixture of two thereof; the initiator is one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO and tetradecyltrihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphite CPI06 or a mixture of two thereof.
[0017] Preferably, the initiator is a mixture of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide TPO and tetradecyl trihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphite CPI06, and the mass of tetradecyl trihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphite CPI06 is ≤ 2% of the mass of the photosensitive resin.
[0018] Preferably, in S2, the mixed material is subjected to 5-10 rounds of roller milling with a three-roll mill at a feed gap of 80-30 μm and a rotation speed of 50-150 r / min.
[0019] Preferably, in S2, a ceramic slurry having a viscosity of 8000-14000 cps is obtained by roller milling.
[0020] Preferably, in S3, the extrusion speed of the extrusion device is 1000-3000 mm / min, the slurry in the heating chamber is heated to 30-50° C., the nozzle diameter used at the extrusion port is 0.2-0.8 mm; and the light intensity of the light source is 30-100 mW.
[0021] Preferably, in S4, during the debinding process, the heating rate is 0.2-0.5°C / min, the temperature is raised to 900-1100°C, and the temperature is kept for 2-4 hours; during the sintering process, the heating rate is 3°C / min, the temperature is raised to 1780°C, and the temperature is kept for 2 hours.
[0022] Preferably, the purity of the ceramic powder is ≥99.99%.
[0023] Preferably, the amount of the dispersant used is 1% to 5% of the mass of the ceramic powder.
[0024] Preferably, in S1, during the ball milling process, the ball milling speed is 300-400 r / min, and the ball milling time is 2-4 h.
[0025] The present invention also provides a transparent ceramic fiber, which is prepared by adopting the preparation method of the transparent ceramic fiber.
[0026] The present invention proposes a method for preparing transparent ceramic fiber by slurry extrusion photocuring, wherein the selected ceramic powder, photosensitive resin, dispersant and initiator are ball-milled to obtain a mixture, the obtained mixture is homogenized and roll-milled in a 3D roller mill, the slurry is evenly mixed and maintained at a moderate viscosity, the obtained slurry is placed in an extrusion molding machine including a photocuring lamp to obtain a molded fiber blank, a cellulose blank is obtained after debinding, and a transparent ceramic fiber is obtained after curing. The present invention utilizes the process of adding multiple roller millings after ball milling and extrusion photocuring instead of extrusion natural curing, and utilizes the characteristics of increased slurry uniformity after multiple roller milling, which can increase the uniformity and qualified rate of the green blank and improve the quality of the ceramic; by curing and collecting the streamlines of the extruded slurry while falling, the upper limit of the length of the extruded fiber can be broken, and the strength of the blank can be accurately and freely controlled by changing the light intensity conditions, reducing the deformation of debinding and sintering.
[0027] The present invention realizes liquid extrusion to prepare transparent ceramic fibers by combining photocuring technology with extrusion molding technology, solves the problems of high surface roughness and poor optical performance caused by traditional extrusion processes, and realizes stable long-distance fiber preparation. Its advantages include but are not limited to: 1) It can realize continuous extrusion preparation of high aspect ratio and low defect ceramic fibers. The fiber length is controllable, the roundness is high, the thickness is controllable, and the preparation diameter is ≤200μm. 2) Through photocuring technology, the fiber surface is uniformly cured, which can improve the uniformity, density and mechanical properties of the fiber; 3) The fiber shape is self-rounded by surface tension, and the obtained fiber does not require post-processing such as polishing the curved surface. The process is simple and has industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the device used for extrusion photocuring preparation in an embodiment of the present invention;
[0029] Figure 2 The microscopic morphology of the wire obtained in step 3 of Example 2 of the present invention;
[0030] Figure 3 This is a length diagram of the wire obtained in step 3 of Example 2 of the present invention;
[0031] Figure 4 This is a transparent effect diagram of the fiber obtained after sintering in Example 2 of the present invention;
[0032] Figure 5 This is a morphology diagram of the fiber obtained after sintering in Example 2 of the present invention;
[0033] Figure 6 This is a microscopic picture of the fiber obtained after sintering in step 4 of comparative example 1 of the present invention;
[0034] Figure 7 The microscopic morphology of the formed wire obtained in step 2 of comparative example 2 of the present invention;
[0035] Figure 8 This is a morphology diagram of the fiber obtained after sintering in Comparative Example 2 of the present invention;
[0036] Fig. 9 This is a physical picture of the product prepared in Example 1 of the present invention;
[0037] Fig.10 This is a micrograph of the fiber obtained after sintering in Example 1 of the present invention;
[0038] Fig.11 This is a physical picture of the product prepared in Comparative Example 1 of the present invention;
[0039] Fig.12 This is a physical picture of the product prepared in Comparative Example 3 of the present invention;
[0040] Fig.13 This is a physical picture of the product prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0043] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0044] The schematic diagram of the extrusion molding device used below is as follows Figure 1 As shown, it includes a motor (specifically a stepper motor), an extrusion bolt, a feeding chamber, a slurry flow channel and a heating system (specifically a heating strip). The stepper motor transmits torque to the extrusion bolt to extrude the slurry mixed in the feeding chamber toward a nozzle in the slurry flow channel (the nozzle diameter is 0.35 mm) to form a continuous slurry flow line. The heating system is responsible for controlling the temperature in the slurry flow channel to be constant. The slurry flow line is cured and formed after being irradiated by a curing light source (LED light source).
[0045] Manufacturer of the dispersant used: Jiaxing Raoji Technology Co., Ltd.
[0046] Example 1
[0047] This embodiment is a slurry extrusion light curing molding preparation method of yttrium aluminum garnet transparent ceramic fiber, comprising the following steps:
[0048] Step 1, ball milling and mixing: Weigh ceramic powder, photosensitive resin, dispersant and initiator according to 83.64wt.% solid content, where ceramic powder is a mixture of yttrium oxide and aluminum oxide in a molar ratio of 3:5, photosensitive resin is a mixture of HEA and HDDA in a mass ratio of 3:4, accounting for 13.07wt.% of the total mass, dispersant CPD01 is used, the amount is 3% of the mass of ceramic powder, initiator TPO is used, the amount is 6% of the mass of photosensitive resin. After conversion, the specific proportions of each raw material in this process are shown in the following table:
[0049]
[0050]
[0051] After weighing the raw materials, they were mixed in a planetary ball mill at 400 r / min for 3 h to obtain a mixed material;
[0052] Step 2, roller milling: Place the mixture obtained in step 1 in a three-roll mill with a feed gap of 80 μm, a discharge gap of 40 μm, and roll mill the mixture for 5 rounds at 150 r / min to obtain a ceramic slurry with a viscosity of 11000 cps;
[0053] Step 3: extrusion photocuring: the ceramic slurry obtained in step 2 is introduced into the feeding chamber of the extrusion molding device preheated at 35°C, extruded at a speed of 1500 mm / min to form a falling streamline, and flows through a ring light source, and cured at a light intensity of 35 mW to obtain a molded fiber filament;
[0054] Step 4, debinding and sintering: The wire obtained in step 3 is heated to 1000℃ in a muffle furnace at 0.3℃ / min, pre-sintered for 2h to remove organic matter, and a cellulose blank is obtained. Then the temperature is raised to 1780℃ at 3℃ / min and kept at this temperature for 2h to obtain a dense sample of yttrium aluminum garnet transparent ceramic fiber, the micrograph of which is shown in the figure. Fig.10 As shown by Fig.10 It can be seen that there are some small pores on the surface of the sample; the actual picture is as follows Fig. 9 As shown by Fig. 9 It can be seen that the sample has a certain degree of transparency.
[0055] Example 2
[0056] This embodiment is a method for preparing alumina transparent ceramic fibers by slurry extrusion and photocuring, comprising the following steps:
[0057] Step 1, ball milling and mixing: Weigh ceramic powder, photosensitive resin, dispersant and initiator according to 81.04wt.% solid content, where the ceramic powder is 4N grade alumina powder, the photosensitive resin is a mixture of HEA, HDDA, TMPTA in a mass ratio of 1:1:1, accounting for 16.21wt.% of the total mass, the dispersant is CPD01, the amount is 3% of the mass of the ceramic powder, the initiator is a mixture of TPO and CPI06 in a mass ratio of 1:1, the amount is 2% of the mass of the photosensitive resin. After conversion, the specific weighing ratio of each raw material in this process is shown in the following table:
[0058]
[0059] After weighing the raw materials, they were mixed in a planetary ball mill at 350 r / min for 4 h to obtain a mixed material;
[0060] Step 2, roller milling: Place the mixture obtained in step 1 in a three-roll mill with a feed gap of 80 μm, a discharge gap of 50 μm, and roll mill the mixture for 7 rounds at 150 r / min to obtain a ceramic slurry with a viscosity of 9000 cps;
[0061] Step 3: Extrusion photocuring: The ceramic slurry obtained in step 2 is introduced into the feeding chamber of the extrusion molding device preheated at 35°C, extruded at a speed of 2100 mm / min to form a falling streamline, and flows through a ring light source, and cured at a light intensity of 35 mW to obtain a molded fiber filament, the surface morphology of which is shown in the figure. Figure 2 As shown by Figure 2 It can be seen that the obtained fiber filaments have high roundness and small radius (≤200 μm), and their length can reach 30 cm. Figure 3 As shown;
[0062] Step 4: Debinding and sintering: The wire obtained in step 3 is heated to 900℃ in a muffle furnace at 0.3℃ / min, pre-sintered for 3h to remove organic matter, and a cellulose blank is obtained. Then the temperature is raised to 1780℃ at 3℃ / min and kept at this temperature for 2h to obtain a dense sample of alumina transparent ceramic fiber, the morphology of which is shown in the figure. Figure 5 As shown by Figure 5 It can be seen that the fiber cross section is dense, without any pores, and the surface is smooth. The actual transparent effect is as shown in the figure Figure 4 As shown by Figure 4 It can be seen that it has transparent properties and the text under the fibers is clearly visible.
[0063] Comparative Example 1
[0064] This comparative example is a method for preparing alumina transparent ceramic fibers by slurry extrusion and photocuring, comprising the following steps:
[0065] Step 1, ball milling mixing: weigh ceramic powder, photosensitive resin, dispersant and initiator according to 86.38wt.% solid content, wherein the ceramic powder is 4N grade alumina powder, the photosensitive resin is a mixture of HEA, HDDA, and TMPTA in a mass ratio of 3:4:3, accounting for 10.5wt.% of the total mass, the dispersant is CPD01, and the amount is 3% of the mass of the ceramic powder, and the initiator is a mixture of TPO and CPI06 in a mass ratio of 1:1, and the amount is 5% of the mass of the photosensitive resin.
[0066] After conversion, the weighing ratio of each raw material in this process is shown in the following table:
[0067]
[0068] After weighing the raw materials, they were mixed in a planetary ball mill at 400 r / min for 4 h to obtain a mixed material;
[0069] Step 2, roller milling: Place the mixture obtained in step 1 in a three-roll mill with a feed gap of 60 μm, a discharge gap of 50 μm, and roll mill the mixture for 7 rounds at 150 r / min to obtain a ceramic slurry with a viscosity of 9000 cps;
[0070] Step 3: extrusion photocuring: the ceramic slurry obtained in step 2 is introduced into the feeding chamber of the extrusion molding device preheated at 35°C, extruded at a speed of 2100 mm / min to form a falling streamline, and flows through a ring light source, and cured at a light intensity of 35 mW to obtain a molded fiber filament;
[0071] Step 4: Debinding and sintering: The wire obtained in step 3 is heated to 1100℃ in a muffle furnace at 0.25℃ / min, pre-sintered for 3h to remove organic matter, and a cellulose blank is obtained. Then the temperature is raised to 1780℃ at 3℃ / min and kept at this temperature for 2h to obtain a dense sample, as shown in the micrograph. Figure 6 As shown in the actual picture Fig.11 As shown by Figure 6 and 11 It can be seen that its surface is relatively rough.
[0072] Comparative Example 2
[0073] This embodiment is a slurry extrusion light-curing molding method for yttrium aluminum garnet ceramic fiber without roller grinding, comprising the following steps:
[0074] Step 1, ball milling and mixing: Weigh ceramic powder, photosensitive resin, dispersant and initiator according to 83.64wt.% solid content, where ceramic powder is a mixture of yttrium oxide and aluminum oxide in a molar ratio of 3:5, photosensitive resin is a mixture of HEA and HDDA in a mass ratio of 3:4, accounting for 13.07wt.% of the total mass, dispersant CPD01 is used, the amount is 3% of the mass of ceramic powder, initiator TPO is used, the amount is 6% of the mass of photosensitive resin. After conversion, the specific weighing ratio of each raw material in this process is shown in the following table:
[0075]
[0076] After weighing the raw materials, they were mixed in a planetary ball mill at 400 r / min for 3 h to obtain a mixed material;
[0077] Step 2: Extrusion photocuring: The ceramic slurry obtained in step 1 is introduced into the feeding chamber of the extrusion molding device preheated at 35°C, extruded at a speed of 2100 mm / min to form a falling streamline, and flows through a ring light source, and cured at a light intensity of 35 mW to obtain a molded fiber filament; its microscopic picture is as follows Figure 7 As shown by Figure 7 It can be seen that it is not very round and has large pores;
[0078] Step 3, debinding and sintering: The wire obtained in step 2 is heated to 1000℃ in a muffle furnace at 0.3℃ / min, pre-sintered for 2h to remove organic matter, and a cellulose blank is obtained. Then the temperature is raised to 1780℃ at 3℃ / min and kept at this temperature for 2h to obtain a dense sample, as shown in the micrograph. Figure 8 As shown by Figure 8 It can be seen that its roundness is not high.
[0079] Comparative Example 3
[0080] The only difference from Example 2 is that the initiator uses a mixture of TPO and CPI06 in a mass ratio of 1:1, and the amount used is 5% of the mass of the photosensitive resin; the obtained fiber diameter is uneven, such as Fig.12 shown.
[0081] Comparative Example 4
[0082] The only difference from Example 2 is that: no roller milling is performed; the obtained fiber is opaque, such as Fig.13 shown.
[0083] Figure 4 , Fig. 9 , Fig.11 , Fig.12 The text in the figure is the shooting background, which is convenient for observing the transparency of the fiber.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a transparent ceramic fiber, characterized in that: The following steps are involved: S1, ball-milling ceramic powder, photosensitive resin, dispersant and initiator to obtain a mixture; wherein the mass ratio of the ceramic powder, photosensitive resin, dispersant and initiator is 81-84:13-16.5:0.8-4.2:0.3-0.8; S2, roller-milling the obtained mixture to obtain a ceramic slurry; S3, extruding the obtained ceramic slurry in a preheated extrusion device, and passing through a light source for curing to obtain a formed fiber filament; S4, debinding and sintering the obtained shaped fiber filaments to obtain the transparent ceramic fiber.
2. The method for preparing the transparent ceramic fiber according to claim 1, characterized in that: In S1, the ceramic powder is a mixture of one or more of alumina powder, yttrium oxide powder and magnesium oxide powder.
3. The method for preparing the transparent ceramic fiber according to claim 1, characterized in that: In S1, the photosensitive resin is a mixture of one or more of hydroxyethyl acrylate, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate.
4. The method for preparing the transparent ceramic fiber according to claim 1, characterized in that: In S1, the dispersant is one of CPD01 and CPD02 or a mixture of two thereof; the initiator is one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and tetradecyltrihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphorous acid or a mixture of two thereof.
5. The method for preparing the transparent ceramic fiber according to claim 4, characterized in that: The initiator is a mixture of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide and tetradecyl trihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphorous acid, and the mass of the tetradecyl trihexylphosphine bis(2,4,4-trimethylpentyl) hypophosphorous acid is less than or equal to 2% of the mass of the photosensitive resin.
6. The method for preparing the transparent ceramic fiber according to claim 1, characterized in that: In S2, the mixed material is subjected to 5-10 rounds of roller milling using a three-roll mill at a feed gap of 80-30 μm and a rotation speed of 50-150 r / min.
7. The method for preparing transparent ceramic fiber according to claim 1, characterized in that: In S2, a ceramic slurry having a viscosity of 8000-14000 cps is obtained by roll milling.
8. The method for preparing transparent ceramic fiber according to claim 1, characterized in that: In S3, the extrusion speed of the extrusion device is 1000-3000 mm / min, the slurry in the heating chamber is heated to 30-50° C., the nozzle diameter used at the extrusion port is 0.2-0.8 mm; and the light intensity of the light source is 30-100 mW.
9. The method for preparing a transparent ceramic fiber according to any one of claims 1 to 8, characterized in that: In S4, during the debinding process, the heating rate is 0.2-0.5°C / min, the temperature is raised to 900-1100°C, and the temperature is kept for 2-4h; During the sintering process, the heating rate was 3°C / min, the temperature was raised to 1780°C, and the temperature was kept for 2h.
10. A transparent ceramic fiber, characterized in that: The transparent ceramic fiber is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of aluminum oxide ceramic continuous fiber
CN102965764A
High-performance microwave dielectric ceramic and photocuring manufacturing method thereof
CN111302785A
Method for preparing transparent ceramic through one-time forming based on photocuring 3D printing technology
CN114800767A
Glass-based solid electrolyte in field of solid-state batteries and preparation method of glass-based solid electrolyte
CN117878392A
Method for preparing dentiform shaped ceramics
WO2017092013A1